FUJIFILM: Fujifilm FinePix S9600: improving an enthusiasts' favourite; Powerful digital camera with SLR-like body refines the popular FinePix S9500 (M2 Presswire, 2006)
Fujifilm today announced the release of the FinePix S9600, replacement to the critically acclaimed FinePix S9500 and the new flagship in Fujifilm's range of 'prosumer' digital cameras. The new model features carefully considered modifications designed to improve image quality as well as making it easier to use and better performing in low light. Refinements include increased image sharpness, a more generous LCD screen, faster autofocus in low light and improvements to the camera's flash capability. These features combine with existing Fujifilm technologies to result in user- friendliness more usually associated with compact digital cameras, and a performance to challenge entry-level digital SLRs. Fujifilm continually strives to achieve better performance in low light. In these conditions, the FinePix S9600 has an autofocus response time that is up to 40 per cent quicker than its predecessor. In addition to the camera's 0.01 second shutter-lag and 0.8 second start-up time, this means that images can be composed and captured almost instantaneously. Combined with Fujifilm's acclaimed high ISO performance, which combats image blur caused by subject movement as well as camera shake, the FinePix S9600's responsiveness makes it an ideal tool for enthusiast photographers looking to photograph fast paced subjects such as those at sporting events or in the wild. FinePix S9600 features at a glance (new features are in bold): *Super CCD HR sensor delivering nine million effective pixels *Real Photo Processor II reduces noise and delivers enhanced colour reproduction *New Fujinon 10.7x (28-300mm) fixed optical zoom lens with manual twist barrel control *Sensitivity setting of ISO 1600 at full resolution for low light photography with reduced noise *Low sensitivity of ISO 80 for ultra-high quality photography *Ultra- fast response times (0.01 second shutter lag and 0.8 second start- up) *Improved autofocus response time in low light conditions *Improved image processing algorithms resulting in increased image sharpness and resolution *Intelligent Flash system *2.0" (230,000 pixel) tilting LCD screen for easy high and low angle shooting *Hyper Utility Software HS-V2 version 3 for RAW format shooting *Real-time histogram to assist exposure settings before shooting *Highlight Warning feature for displaying highlight areas in playback *TV-quality VGA movie recording of 30 frames per second with sound *Closed unit design to eliminate dust accumulation on the CCD *Hotshoe and PC sync terminal *Both xD-Picture Card(tm) and Compact Flash(tm)/Microdrive compatible *PictBridge(tm) compatible for direct printing without a PC